Adverse Pregnancy Outcomes in Overweight and Obese Pregnant Women Visiting a Tertiary Care Center in Western Nepal: A Prospective Cohort Study - Shrestha, Deepak; Singh, Kritina; Aryal, Shreyashi (Journal of Lumbini Medical College, 2021)
Introduction: Maternal obesity is an established risk factor for various adverse pregnancy outcomes. For instance, increased chances of labour induction, prolonged labour, instrumental and cesarean deliveries, medical disorders of pregnancy, post partum haemorrhage, preterm deliveries, macrosomia, and low Apgar score are well recognised risks of maternal obesity. This study aimed to evaluate these maternal and fetal outcomes in relation to the maternal body mass index (BMI). Methods: A prospective cohort study involving 115 overweight and obese women was conducted. Various maternal and fetal outcomes were studied and compared with those of 115 postpartum women with normal BMI. Statistical analysis was done using student's t-test and Chi square test. Binomial logistic regression analysis was carried out to examine the magnitude and significance of the independent effect of BMI. Results: The three groups were comparable in terms of maternal age and gestational age at delivery. The total blood loss was significantly higher in the obese group as compared to the normal BMI (p=0.001) or overweight groups (p=0.005). Vaginal delivery was 69% less common in the obese group in comparison to the normal BMI group. The prevalence of meconium-stained liquor, labour induction, preterm labour, and neonatal intensive care unit admission were not significantly different across the three groups. Conclusion: This study highlighted the increased risk of total blood loss and birth weight >3500 grams with increasing BMI of pregnant women. A multicentric prospective study with larger sample size would shed further light on the strength of association between maternal BMI and various outcomes.